การเปรียบเทียบการรับรู้การดูแลผู้ป่วยด้านจิตวิญญาณของบุคลากรทางการพยาบาลในงานการพยาบาลผู้ป่วยทั่วไปฯ โรงพยาบาลมหาราชนครเชียงใหม่ - อิสรีย์ เขื่อนสุวรรณ (Faculty of Medicine, Chiang Mai University, 2019)
Chiang Mai Medical Journal (Formerly Chiang Mai Medical Bulletin) is an official journal of the Faculty of Medicine, Chiang Mai University. It accepts original papers on clinical and experimental research that are pertinent in the biomedical sciences. The Journal is published 4 issues/year (i.e., Mar, Jun, Sep, and Dec). Original articles, review articles, brief reports, case reports, and miscellany (editorials, perspectives, opinions, and letters to the editor) are welcome. All manuscripts submitted to Chiang Mai Medical Journal must not have been previously published (except in abstract form) or under consideration for publication elsewhere. Each submitted article will be reviewed by two referrees or more. Following publication, Chiang Mai Medical Journal reserves the copyright of all published materials and such materials may not be reproduced in any form without written permission from Chiang Mai Medical Journal. We strongly recommend that authors follow the guideline in manuscript preparation below. Failure to comply with the instruction will result in delay the processing of your paper